Physician–patient communication at diagnosis of type 2 diabetes and its links to patient outcomes: New results from the global IntroDia® study. (May 2017) - Polonsky, William H.; Capehorn, Matthew; Belton, Anne; Down, Susan; Alzaid, Aus; Gamerman, Victoria; Nagel, Friedericke; Lee, Jisoo; Edelman, Steven
Highlights: Patients with type 2 diabetes were surveyed about their diagnosis consultation. Physician conversation 'elements' were identified by exploratory factor analysis. Good physician communication at diagnosis may enhance patient-reported outcomes. Abstract: Aims: To investigate patient experiences during the diagnosis of type 2 diabetes mellitus (T2DM), focusing on how physician–patient communication at diagnosis influences patients' psychosocial stress and subsequent self-management and outcomes. Methods: We surveyed adults with T2DM in 26 countries in a large cross-national study of physician–patient communication during early T2DM treatment (IntroDia®). The self-report questionnaire assessed retrospectively patient experiences during diagnosis conversations (focusing on 43 possible conversational elements, and communication quality) and potential effects on patient-reported outcomes. Results: Data from 3628 people with T2DM who had been prescribed oral treatment at diagnosis were analysed. Exploratory factor analyses of the conversational elements yielded four coherent, meaningful factors: Encouraging (Cronbach's α = 0.86); Collaborative (α = 0.88); Recommending Other Resources (α = 0.75); and Discouraging (α = 0.72). Patient-perceived communication quality (PPCQ) at diagnosis was positively associated with Encouraging (β = +1.764, p  < 0.001) and Collaborative (β = +0.347, p  < 0.001), negatively associated with Discouraging (β = −1.181, p  < 0.001) and not associated with Recommending Other Resources (β = +0.087, p  = 0.096), using a stable path model. PPCQ was associated with less current diabetes distress, greater current well-being and better current self-care. Conversation elements comprising factors associated with better PPCQ (Encouraging and Collaborative) were recalled more frequently by patients than elements associated with poor PPCQ (Discouraging). Conclusions: Better physician–patient communication at T2DM diagnosis may contribute to subsequent greater patient well-being and self-care, and may be enhanced by greater physician use of Collaborative and Encouraging conversation elements.